Understanding Customer Satisfaction in Budget Airlines: A Malaysian Case Study - Lay Hong Tan; Choon Ling Sim; Jia Hui Tan; Jing Hui Tan; Ke Rou Tan; Qiu Yu Tan; Shi Wei Tan; A. J. Ali; Daisy Mui Hung Kee (International Journal of Tourism and Hospitality in Asia Pasific, 2025)
Customer satisfaction is a crucial determinant of brand loyalty and long-term success in the competitive airline industry. Low-cost carriers, in particular, must continually enhance service quality to maintain customer trust and market advantage. This study aims to examine the factors influencing customer satisfaction among passengers of low-cost airlines in Malaysia. A quantitative research design was employed using an online questionnaire distributed via social media to frequent travelers, resulting in 150 valid responses. Data were analyzed using regression analysis, with customer satisfaction as the dependent variable and perceived convenience, perceived benefits, perceived security and privacy, and perceived trust as independent variables. The results show that perceived convenience (? = 0.110), perceived security and privacy (? = 0.210), and perceived trust (? = 0.334) have positive and significant effects on customer satisfaction, while perceived benefits (? = –0.026) show a minor negative relationship. The model explains 26.5% of the variance in customer satisfaction and is statistically significant (F = 14.555, Durbin-Watson = 1.825). These findings highlight the importance of building customer trust, ensuring transaction security, and enhancing convenience to strengthen satisfaction and loyalty. The results provide practical insights for low-cost airlines to improve service quality and sustain competitiveness in Malaysia’s aviation market.